Privasi Dan Etika Dalam Manajemen Sumber Daya Manusia Digital - Siti Nur Eliza Rahmawati; Maulinda Hasanah; Ainur Rohmah; Rizki Adytia Putra Pratama; M Isa Anshori (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Data ethics is part of what we mean when we talk about the decisions and actions we take when collecting, analyzing, and using data. and actions we take when collecting, analyzing and using data. The principles and laws specific to data use in each country must be followed. Ethics is not just about taking responsibility; if we are not careful and ethical in our in our activities on social media, we will suffer consequences and break the law. Ethics in the digital world can be seen from various perspectives, including ethics of personal use, business ethics, political ethics, and others. In addition to ethics, in the digital world there is also something called privacy policy. Privacy policy emerged from the common law system, system as a self-regulatory approach. Privacy policies are tailored to the principles of personal data protection principles established by national laws and regulations. There are ethical issues in the utilization of big data that need to be addressed. Decision-making based on data may become biased and unfair due to improper data analysis. Big data is a trend that covers every field of technology.